Developing a Model of Monitoring Innovative Activity in Pedagogical Colleges - Mexro’zbek Muxtorjon o’g’li Jo’raboyev; Tursunova Zulxumor Jobir qizi (Academia One Publishing, 2023)
In the ever-evolving landscape of education, the integration of innovative activities within pedagogical colleges is paramount. Monitoring these activities is crucial for ensuring their effectiveness and aligning them with educational goals. This article proposes a comprehensive model of monitoring innovative activity in pedagogical colleges, aiming to provide a structured framework for assessing, analyzing, and enhancing the impact of innovative practices
Keywords: assessing; analyzing; enhancing; integration